Epidemiological characteristics of Brazilian spotted fever in Minas Gerais State, Brazil, 2000-2008 - Frederico Figueiredo Amâncio; Vânia Dutra Amorim; Talita Leal Chamone; Mariana Gontijo de Brito; Simone Berger Calic; Anamaria Cordeiro Leite; Gabriela Lobato Fraga; Marcela Lencine Ferraz
Brazilian spotted fever is the most common rickettsiosis in Brazil, most prevalent in the States of São Paulo and Minas Gerais. The aim of this study was to describe the epidemiological characteristics of Brazilian spotted fever in Minas Gerais from 2000 to 2008. Of the 132 cases of Brazilian spotted fever, 53 patients died, representing a case-fatality rate of 40.2%. Males predominated, with 78.8% of confirmed cases, and median age was 26.5 years. Absence of rash was associated with increased risk of death (p = 0.005). Greater Metropolitan Belo Horizonte, Rio Doce Valley, and Zona da Mata accounted for 70.6% of the cases, which occurred mainly from May to November. There was an increase in the number of cases, which could suggest an expansion of the disease, but probably resulted from an increase in the health system's diagnostic capacity and sensitivity. Despite this improvement, the case-fatality rate remains high and with no apparent tendency to decrease, thus indicating the need for improved prevention and patient care.